Assessment of acute thermal damage volumes in muscle using magnetization‐prepared 3D T2‐weighted imaging following MRI‐guided high‐intensity focused ultrasound therapy. Issue 2 (9th January 2017) - Staruch, Robert M.; Nofiele, Joris; Walker, Jamie; Bing, Chenchen; Madhuranthakam, Ananth J.; Bailey, April; Kim, Young‐Sun; Chhabra, Avneesh; Burns, Dennis; Chopra, Rajiv
Abstract : Purpose: To evaluate magnetization‐prepared 3D T 2 ‐weighted magnetic resonance imaging (MRI) measurements of acute tissue changes produced during ablative MR high‐intensity focused ultrasound (MR‐HIFU) exposures. Materials and Methods: A clinical MR‐HIFU system (3T) was used to generate thermal lesions ( n = 24) in the skeletal muscles of three pigs. T 1 ‐weighted, 2D T 2 ‐weighted, and magnetization‐prepared 3D T 2 ‐weighted sequences were acquired before and after therapy to evaluate tissue changes following ablation. Tissues were harvested shortly after imaging, fixed in formalin, and gross‐sectioned. Select lesions were processed into whole‐mount sections. Lesion dimensions for each imaging sequence (length, width) and for gross sections (diameter of lesion core and rim) were assessed by three physicists. Contrast‐to‐background ratio between lesions and surrounding muscle was compared. Results: Lesion dimensions on T 1 and 2D T 2 ‐weighted imaging sequences were well correlated (R 2 ∼0.7). The contrast‐to‐background ratio between lesion and surrounding muscle was 7.4 ± 2.4 for the magnetization‐prepared sequence versus 1.7 ± 0.5 for a conventional 2D T 2 ‐weighted acquisition, and 7.0 ± 2.9 for a contrast‐enhanced T 1 ‐weighted sequence. Compared with diameter measured on gross pathology, all imaging sequences overestimated the lesion core by 22–33%, and underestimated the lesion rim by 6–13%. Conclusion: After MR‐HIFU exposures, measurements of the acute thermal damage patterns in muscle using a magnetization‐prepared 3D T 2 ‐weighted imaging sequence correlate with 2D T 2 ‐weighted and contrast‐enhanced T 1 ‐weighted imaging, and all agree well with histology. The magnetization‐prepared sequence offers positive tissue contrast and does not require IV contrast agents, and may provide a noninvasive imaging evaluation of the region of acute thermal injury at multiple times during HIFU procedures. Level of Evidence: 1 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2017;46:354–364